The Relationship of Respectful Midwifery Care (RMC) Evaluation to Satisfaction of Midwifery Services from the Mother's Perspective in the North Jakarta Region - Heriza Syam; Hamdah Ridhaka Waljannah; Wa Ode Hajrah; Rosni Lubis; Ani Kusumastuti; Nina Primasari; Aticeh (Public Health of Indonesia)
Background: The labor process represents a critical phase in ensuring maternal and neonatal safety. The quality of care provided by midwives during this period plays a vital role in determining health outcomes for both mothers and newborns. To achieve optimal care, midwives are required to possess competencies in line with the standards recommended by the International Confederation of Midwives (ICM), including the implementation of Respectful Midwifery Care (RMC). The concept of RMC has also been promoted by the Indonesian Midwives Association (IBI) as an essential component of quality midwifery services. However, empirical evidence on the implementation of RMC in Indonesia remains limited. This gap highlights the need to explore women’s perspectives on the application of RMC and its association with maternal satisfaction.